Transformative Multicultural Educational Games: Enhancing Literacy and Critical Thinking Skills in Elementary Schools - Maharani, Ni Luh Gede Putri; Widiana, I Wayan (Universitas Pendidikan Ganesha, 2024)
This study is motivated by the low literacy and critical thinking skills observed among students in the classroom. The purpose of this research is to develop an educational game media with a transformative multicultural approach that aligns with Indonesia's multicultural society. The study focuses on analyzing the content validity of the media, students' responses to the media, and its effectiveness in enhancing literacy and critical thinking skills. The research employs the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subject of the research is an educational game media with a transformative multicultural approach, while the objects include the validity, practicality, and effectiveness of the media. Data were collected through questionnaires, tests, and interviews with homeroom teachers. Data analysis was conducted using both quantitative and qualitative descriptive methods. The findings indicate that the educational game media exhibits a high level of content validity. Students' responses to the practicality of the media were highly positive, and the media was proven to significantly enhance students' literacy and critical thinking skills. The conclusion of this study is that the transformative multicultural educational game media can serve as an effective and relevant learning tool to support the development of students' competencies in elementary schools.